Chronic disease, depression, and adult attachment within romantic relationships: a longitudinal analysis of trajectories of physical health - Brown, Cameron Clark (Kansas State University, 2017)
Despite previous literature illustrating strong links between social relations, mental health, and health outcomes, much remains unknown regarding the associations among adult romantic attachment, depression, and reports of physical health within those diagnosed with a chronic disease. Using a sample of 197 individuals who reported a diagnosed chronic disease and in a cohabiting or romantic relationship from the Flourishing Families Project, a mediated latent growth curve analysis was used to test to what extent trajectories of reported physical health across two years were a function of attachment and depression. Specifically, trajectories of physical health were modeled to examine changes over two years with time-invariant covariates of depressive symptoms and adult attachment predicting initial levels of physical health and changes in physical health over time. Results indicated that as depressive symptoms increased, initial levels of physical health were worse. Higher reports of attachment anxiety were linked with better initial reports of physical health. Further, higher reports of depressive symptoms and attachment anxiety predicted a significant upward shift in the expected trajectory of improved physical health. These results expand current research and theory by examining how adult attachment and depression are linked with expected trajectories in physical health over time.
Keywords: Relationships; Attachment; Depression; Health; Chronic disease